Formal Aspects in SDH for Children in Spanish Television: A Descriptive Study - Tamayo, Ana (Estudios de Traducción, 2016)
The comprehension of a subtitle goes far beyond the understanding of the meaning of the words it comprises. Formal aspects of subtitles for the d/Deaf and the hard-of-hearing (SDH) can be crucial in the cognitive effort necessary to process the subtitle within its audiovisual context (Perego 2008). The present article studies common practices of formal aspects in SDH for children, focusing on three parameters: layout and positioning of the subtitle; orthotypographic conventions; and resources for the identification of characters in the three TV channels dedicated exclusively to the youngest audiences in Spain. The present piece of research was carried out by analysing and evaluating these three parameters in comparison with the current UNE Standard 153010 (AENOR 2012) and with previous theoretical studies in the field.
Keywords: Subtitling; SDH; audiovisual translation; accessibility; children; layout.